Economic Nationalism and the Us-China Trade War: Deploying the Thucydides Trap Analysis - Fregene, Patrick Akpieyi Appearance (Communicate: Journal of Library and Information Science, 2025)
The world is being inundated by the weaponization of tariffs in cross-border trade, leading to a trade war between the United States (US) and China, with a few other states such of Canada, South Korea and Mexico, already affected. This war makes nonsense of the ideal of globalization, a concept formulated by the Liberals to describe global interconnectivity, socio-cultural exchanges and removal of trade barriers in international trade. This distortion to global trade by these most developed economies of the world requires the attention of students of political economy, hence this study. This study seeks to examine the reasons for the imposition of high tariffs by the US and the retaliatory actions taken by receiving states. The theory of the Thucydides trap was deployed to analyze the work. Thucydides traced the cause of the Peloponnesian war of old Greek empire between Sparta and Athens and locate it on the rivalry between a dominant and rising state, respectively. Among others, the study found that for the US to maintain her dominance in global politics, the adventurism of China, a rising state must be clipped; hence the trade war. The study recommends that states involved in cross-border trade should have a comprehensive trade agreement in place to regulate their trade relationships.